3D Planning and Treatment Outcomes of Bone Anchored Maxillary Protraction - Nguyen, Tung (Cone Beam Computed Tomography in Orthodontics: Indications, Insights, and Innovations, 2014)
This chapter provides a review of the current status of protocols used for bone anchored maxillary protraction (BAMP) and the treatment outcomes in three‐dimensional (3D) when using this approach to correct Class III malocclusion. Treatment outcomes of the BAMP protocol until recently have been studied using conventional two‐dimensional (2D) imaging. Recent advances of 3D radiographic imaging in dentistry have made it possible to gain substantially greater information than conventional 2D imaging. 3D imaging of subjects who underwent BAMP treatment showed changes in maxillary and mandibular structures that otherwise would be impossible to depict using 2D imaging methods. The findings indicate the utility of this approach in the skeletal and dental correction of Class III malocclusions in the growing patient.